The Relationship between Family Socioeconomic Status and Student Cognitive Achievement in PAI Subjects - Sekarmaji Sirulhaq; Siti Nuhaliza Maulida; Imam Buchori; Solahudin; Zulfikri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research was conducted at SDN Sorogol with the aim of exploring whether there is a significant relationship between family socioeconomic status and students' cognitive achievement in PAI subjects. This study aims to answer the question whether academic achievement can be increased even with limited facilities and infrastructure provided by the family or school. The research methodology used is quantitative with an associative approach, where data is collected through questionnaires, unstructured interviews, closed observation, and documentation. Data analysis steps include data quality tests (instrument validity and reliability), classic assumption tests (data normality), and hypothesis testing (T test, F test, linearity test, and correlation test). The results showed that the alternative hypothesis (Ha) was accepted, while the null hypothesis (Ho) was rejected. This indicates that this study succeeded in proving that there is no significant relationship between family socioeconomic status and students' cognitive achievement in PAI subjects at SDN Sorogol. In other words, these results indicate that although students may have limited facilities and infrastructure, family socioeconomic status factors do not significantly affect student academic achievement in PAI subjects. These results may have important implications in teaching that with proper support from schools and the environment, students' academic achievement is not only determined by their family's socioeconomic status. Other factors such as motivation, educational support, and student effort also play an important role in achieving good academic performance. However, it is important to remember that the results of this study are limited to the context of Sorogol Elementary School and PAI subjects. These results are not automatically applicable to other situations or subjects. In addition, this study has limitations such as the data collection method used and sample size.